Carbon-supported niobium-based bimetallic nitrogen oxide catalyst and its preparation method and application

Through the catalyst preparation method based on carbon-supported niobium-based bimetallic nitrogen oxide, the problem of insufficient activity and stability of non-precious metal ORR catalysts in acidic media in the prior art is solved, and high-efficiency and low-cost catalyst preparation is achieved, which is suitable for Fuel cell, improving ORR performance and stability.

CN115881987BActive Publication Date: 2025-02-14HAINAN UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211500343.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-28
Publication Date
2025-02-14
Estimated Expiration
2042-11-28

AI Technical Summary

Technical Problem

The prior art is difficult to develop efficient, low-cost, and easy to mass-produce non-precious metal oxygen reduction reaction (ORR) catalysts, especially in acidic media, and the catalysts are insufficient in chemical and electrochemical stability, which limits the proton exchange membrane fuel cells. performance.

Method used

Using a catalyst preparation method based on carbon-supported niobium-based bimetallic nitrogen oxide, a precursor solution is prepared by dissolving niobium salt and transition metal salt in water or alcohol solution, and the carbon support is uniformly dispersed in the precursor solution, and filtering and drying and calcination to obtain a carbon-supported niobium-based bimetallic nitrogen oxide catalyst.

Benefits of technology

The catalyst exhibits excellent ORR activity and stability in acidic media, with ORR starting potential up to 0.87V vs.RHE, ORR half-wave potential up to 0.74V vs.RHE, and has good chemical and electrochemical stability, suitable for It is used in fuel cell catalysts, which improves the current density of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115881987B_ABST
    Figure CN115881987B_ABST
Patent Text Reader

Abstract

The present invention provides a catalyst based on carbon-supported niobium-based bimetallic nitrogen oxides and a preparation method and application thereof, which relates to the technical field of fuel cells. The method comprises: dissolving a niobium salt and another transition metal salt in water or an alcohol solution to prepare a precursor solution; uniformly dispersing a carbon carrier in the precursor solution, filtering and drying to obtain a precursor; calcining the precursor with a nitrogen source to obtain a carbon-supported niobium-based bimetallic nitrogen oxide catalyst. The niobium-based bimetallic nitrogen oxide nanoparticles prepared by the present invention are uniformly distributed and have a small particle size, which is conducive to exposing a large number of active sites. The carbon loading makes it have good electrical conductivity. These advantages make it suitable for use in fuel cell catalysts and are conducive to improving the current density of the catalyst. The catalyst has a bimetallic component, which is not only acid-resistant, but also has a rich and adjustable d electronic structure, which can optimize the adsorption strength of the reaction species and obtain excellent catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of fuel cells, and in particular to a carbon-supported niobium-based bimetallic nitrogen oxide catalyst and a preparation method and application thereof. Background Art

[0002] The increasing depletion of traditional fossil energy and the environmental pollution caused by its use have forced people to develop new, cleaner renewable energy and energy conversion technologies. Proton exchange membrane fuel cells are considered to be the most promising type of fuel cell due to their advantages such as high energy conversion efficiency, fast startup and no pollution. The slow kinetics of the cathode oxygen reduction reaction (ORR) is the main factor restricting the performance of proton exchange membrane fuel cells. Pt-based materials are the best ORR catalysts, but Pt is not only expensive, but also extremely scarce, which greatly hinders the commercialization of proton exchange membrane fuel cells. Therefore, the development of cheap and high-performance non-Pt ORR catalysts is of great significance to promoting the large-scale commercialization and sustainable development of proton exchange membrane fuel cells.

[0003] The ORR of proton exchange membrane fuel cells is carried out in an acidic medium, which places very stringent requirements on the catalyst material. The catalyst must have good chemical stability and electrochemical stability in the acidic medium. There are only a few materials that can meet the above conditions, and transition metal nitride is one of them. Transition metal nitride not only has the characteristics of high melting point, high hardness, and acid corrosion resistance, but also has a d electronic structure similar to that of transition metals, and is a highly potential non-precious metal ORR catalyst. A large number of studies have shown that although transition metal nitrides exhibit certain ORR activity, their activity is still far from the requirements of practical applications.

[0004] Therefore, it is necessary to develop a method for preparing high-performance non-precious metal catalysts that is efficient, low-cost, and easy to mass-produce. Summary of the invention

[0005] The present disclosure provides a catalyst based on carbon-supported niobium-based bimetallic nitrogen oxides and a preparation method and application thereof, so as to at least solve the above technical problems existing in the prior art.

[0006] According to a first aspect of the present disclosure, a method for preparing a carbon-supported niobium-based bimetallic oxynitride catalyst is provided, the method comprising:

[0007] Dissolving niobium salt and another transition metal salt in water or alcohol solution to prepare a precursor solution;

[0008] The carbon carrier is uniformly dispersed in the precursor solution, and a precursor is obtained after filtering and drying;

[0009] The precursor is calcined with a nitrogen source to obtain a carbon-supported niobium-based bimetallic oxynitride catalyst.

[0010] In one embodiment, the concentration of the niobium salt in the precursor solution is 0.01-4 mol / L, and the concentration of the transition metal salt is 0.01-4 mol / L.

[0011] In one embodiment, the niobium salt includes one or more of potassium niobate, lithium niobate, sodium niobate, magnesium niobate, niobium oxalate, ammonium niobate oxalate, potassium niobate oxalate, lithium niobate oxalate, sodium niobate oxalate, rubidium niobate oxalate, and ethoxy niobium.

[0012] In one embodiment, the transition metal salt includes one or more of chromium nitrate, chromium chloride, chromium sulfate, chromium acetate, manganese nitrate, manganese chloride, manganese sulfate, manganese acetate, ferric nitrate, ferric chloride, ferric sulfate, ferric acetate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, copper nitrate, copper chloride, copper sulfate, and copper acetate.

[0013] In one embodiment, the niobium-based bimetallic oxynitride includes niobium chromium oxynitride, niobium manganese oxynitride, niobium iron oxynitride, niobium cobalt oxynitride, niobium nickel oxynitride, and niobium copper oxynitride.

[0014] In one embodiment, the carbon carrier includes one of XC-72R carbon black, Ketjenblack carbon black, carbon nanotubes, carbon nanofibers, graphene, MOF-derived carbon, and COF-derived carbon.

[0015] In one embodiment, the precursor is calcined in an atmosphere of ammonia or nitrogen, at a temperature of 150 to 1000° C., for a time of 1 to 5 hours, at a heating rate of 1 to 20° C. / min.

[0016] In one embodiment, the particle size of the carbon-supported niobium-based bimetallic oxynitride nanoparticles is 3 to 50 nm.

[0017] According to a second aspect of the present disclosure, a catalyst based on carbon-supported niobium-based bimetallic oxynitride prepared according to the above method is provided.

[0018] According to a third aspect of the present disclosure, there is provided a use of a carbon-supported niobium-based bimetallic oxynitride catalyst prepared according to the above method in a fuel cell.

[0019] The present invention provides a catalyst based on carbon-supported niobium-based bimetallic nitrogen oxides and a preparation method and application thereof, wherein a niobium salt and another transition metal salt are dissolved in water or an alcohol solution to prepare a precursor solution; a carbon carrier is then uniformly dispersed in the precursor solution, filtered, and dried to obtain a precursor; and finally the precursor is calcined with a nitrogen source to obtain a carbon-supported niobium-based bimetallic nitrogen oxide catalyst. The catalyst exhibits good activity and stability for oxygen reduction reaction and can be used as a cathode catalyst for hydrogen-oxygen fuel cells.

[0020] Compared with the prior art, the catalyst based on carbon-supported niobium-based bimetallic nitrogen oxide and the preparation method thereof of the present invention have the following advantages:

[0021] (1) The present invention proposes a method for preparing carbon-loaded small-particle niobium-based bimetallic oxynitride nanoparticles. The prepared niobium-based bimetallic oxynitride nanoparticles are uniformly distributed and have a small particle size, which is conducive to exposing a large number of active sites. The carbon loading makes them have good electrical conductivity. These advantages make them suitable for use in fuel cell catalysts and are conducive to improving the current density of the catalyst.

[0022] (2) The catalyst prepared by the present invention has a bimetallic component, which is not only acid-resistant, but also has a rich and adjustable d-electronic structure, which can optimize the adsorption strength of the reactants and obtain excellent catalytic performance. The catalyst exhibits excellent catalytic activity and stability for ORR in acidic media, with an ORR onset potential of up to 0.87 V vs. RHE and an ORR half-wave potential of up to 0.74 V vs. RHE. It is one of the best metal nitrogen oxide ORR catalysts in acidic media.

[0023] (3) The present invention adopts an impregnation-filtration method to prepare a carbon-supported niobium-based bimetallic oxynitride precursor, which does not require evaporation of the solvent, saves energy, and is easy to operate, thereby realizing the industrial production and application of the catalyst.

[0024] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, in which:

[0026] In the drawings, the same or corresponding reference numerals represent the same or corresponding parts.

[0027] Figure 1The transmission electron microscope (TEM) image of carbon-supported niobium iron oxynitride prepared in Example 1 of the present disclosure is shown;

[0028] Figure 2 A high-resolution transmission electron microscopy (HR-TEM) image of carbon-supported niobium iron oxynitride prepared in Example 1 of the present disclosure is shown;

[0029] Figure 3 The oxygen reduction linear polarization curves of carbon-supported niobium iron oxynitride and commercial Pt / C catalyst prepared in Example 1 of the present disclosure in an acidic medium after deducting the nitrogen background are shown;

[0030] Figure 4 A comparison chart of the ORR current retention rates of the carbon-supported niobium iron oxynitride prepared in Example 1 of the present disclosure and the commercial Pt / C catalyst in an acidic medium within 30,000 s is shown. DETAILED DESCRIPTION

[0031] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0032] In order to develop a high-performance non-precious metal catalyst that is efficient, low-cost, and easy to mass-produce, the present invention proposes a method for preparing a catalyst based on carbon-supported niobium-based bimetallic nitrogen oxides, characterized in that the method comprises:

[0033] S1. dissolving niobium salt and another transition metal salt in water or alcohol solution to prepare a precursor solution;

[0034] The concentrations of niobium salt and another transition metal salt in the precursor solution are both 0.01-4 mol / L.

[0035] The niobium salt is an oxygen-containing niobium salt, including one or more of potassium niobate, lithium niobate, sodium niobate, magnesium niobate, niobium oxalate, ammonium niobate oxalate, potassium niobate oxalate, lithium niobate oxalate, sodium niobate oxalate, rubidium niobate oxalate, and ethoxy niobium.

[0036] The transition metal salt includes one or more of chromium nitrate, chromium chloride, chromium sulfate, chromium acetate, manganese nitrate, manganese chloride, manganese sulfate, manganese acetate, ferric nitrate, ferric chloride, ferric sulfate, ferric acetate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, copper nitrate, copper chloride, copper sulfate, and copper acetate.

[0037] S2, uniformly dispersing the carbon carrier in the precursor solution, filtering and drying to obtain a precursor;

[0038] The carbon carrier includes one of XC-72R carbon black, Ketjenblack carbon black, carbon nanotubes, carbon nanofibers, graphene, MOF-derived carbon, and COF-derived carbon. The carbon carrier is stirred in the precursor solution for a certain period of time, and a precursor is obtained after filtering and drying.

[0039] S3, calcining the precursor and the nitrogen source to obtain a carbon-supported niobium-based bimetallic oxynitride catalyst.

[0040] The nitrogen source is ammonia or nitrogen, or other nitrogen-containing compounds, which is not limited by the present invention. When nitrogen-containing gas is used as the nitrogen source, the precursor is placed in a tubular furnace with an atmosphere and calcined for a certain period of time, the calcination temperature is 150-1000°C, the calcination time is 1-5h, and the heating rate is 1-20°C / min, and finally a carbon-supported niobium-based bimetallic oxynitride catalyst is obtained. The obtained niobium-based bimetallic oxynitride includes: niobium-chromium oxynitride, niobium-manganese oxynitride, niobium-iron oxynitride, niobium-cobalt oxynitride, niobium-nickel oxynitride, and niobium-copper oxynitride. The particle size of the obtained carbon-supported niobium-based bimetallic oxynitride nanoparticles includes 3-50nm.

[0041] The present invention is described in detail below with reference to specific embodiments.

[0042] Example 1

[0043] A method for preparing a carbon-supported niobium-based bimetallic nitrogen oxide catalyst (NbFeON / ZIF-8-C) comprises the following steps:

[0044] S11, preparing a carbon support ZIF-8-C;

[0045] 10 mmol zinc nitrate and 40 mmol 2-methylimidazole were respectively weighed and dissolved in 70 mL and 30 mL methanol, and then they were mixed and stirred for 12 to 24 hours. The ZIF-8 sample was obtained by centrifugal separation. After oven drying, it was calcined in nitrogen at 900 to 1000°C for 1 to 2 hours to obtain the derivative carbon of ZIF-8 (ZIF-8-C).

[0046] S12, preparation of NbFeON / ZIF-8-C precursor;

[0047] 4-10 mmol of ammonium niobate oxalate and 1-10 mmol of ferric nitrate were respectively weighed and dissolved in 20-40 ml of aqueous solution, and then 0.2-1 g of ZIF-8-C was added thereto. After stirring for 1-2 hours, the mixture was filtered and dried to obtain a NbFeON / ZIF-8-C precursor.

[0048] Preparation of S13, NbFeON / ZIF-8-C catalyst;

[0049] Weigh 0.1-0.5 g of NbFeON / ZIF-8-C precursor and put it into a quartz boat. Then put the quartz boat into a tubular furnace with a quartz tube. First, pass nitrogen for 30-60 minutes to expel the air in the quartz tube. Then switch the nitrogen to ammonia. Raise the temperature from room temperature to 700-900°C at a heating rate of 5-10°C / min. Keep the temperature for 2 hours after reaching the target temperature. Finally, cool it naturally and expel the ammonia in the quartz tube with nitrogen to obtain the final catalyst sample.

[0050] 1. Characterization of catalyst structure and morphology

[0051] Transmission electron microscopy (TEM) was used to observe the morphology of NbFeON / ZIF-8-C catalyst and the morphology of nitrogen oxide nanoparticles. Figure 1 As shown in the figure, the average particle size of NbFeON prepared in this embodiment is 8-15 nm, and the particle size distribution is relatively uniform. Figure 2 The lattice fringes of NbFeON nanoparticles can be clearly seen in medium and high resolution transmission electron microscopy images.

[0052] 2. ORR performance test of catalyst

[0053] A three-electrode system was used to perform linear voltammetric scans in 0.1M HClO4 saturated with oxygen and nitrogen, respectively, at a scan rate of 10 mV / s and an electrode rotation speed of 1600 rpm. The voltammetric curve in 0.1M HClO4 saturated with oxygen was then subtracted from the voltammetric curve in 0.1M HClO4 saturated with nitrogen, as shown in FIG. Figure 3 shown.

[0054] 3. ORR stability test of catalyst

[0055] The stability of the catalyst was tested by chronoamperometry at a constant potential of 0.7 V vs. RHE at an electrode speed of 900 rpm in 0.1 M HClO4 saturated with oxygen for 30,000 s. The ORR current retention rate of the catalyst was recorded every 10,000 s. The results are shown in Table 1. Figure 4 shown.

[0056] Unless otherwise specified, the test method for the ORR performance of the catalyst involved in the present invention in an acidic medium is the same as the above test method.

[0057] The catalyst prepared in this example exhibits excellent ORR performance in an acidic medium, with an ORR onset potential of 0.876 V vs. RHE, an ORR half-wave potential of 0.74 V vs. RHE, and ORR stability being superior to that of a commercial Pt / C catalyst.

[0058] Example 2

[0059] A method for preparing a carbon-supported niobium-based bimetallic nitrogen oxide catalyst (NbCoON / CNT) comprises the following steps:

[0060] S21, pretreatment of carbon carrier;

[0061] Weigh 50-200 mg of carbon nanotubes (CNTs), add them to a 100-500 mL beaker, inject 3 / 5 volume of HNO3 (concentration of 1-4 mol / L) into the beaker, heat and reflux at 70-80 ° C for 8-12 hours, and finally filter the carbon carrier and wash it with deionized water until it is neutral, and then vacuum dry it in an oven at 60-80 ° C for 6-12 hours to obtain a pretreated carbon carrier (CNT). By pretreating the carbon carrier, the defects of the carbon carrier are increased, thereby promoting the adsorption of metal salts by the carbon carrier.

[0062] S22, preparation of NbCoON / ZIF-8-C precursor;

[0063] 1-2 mmol of ethoxyniobium and 1-2 mmol of cobalt chloride were respectively weighed and dissolved in 20-40 ml of ethanol solution, and then 0.2-1 g of pretreated CNT was added thereto, and after stirring for 0.5-1 h, the mixture was filtered and dried to obtain a NbCoON / CNT precursor.

[0064] S23, preparation of NbCoON / CNT catalyst;

[0065] Weigh 0.1-0.5 g of NbCoON / CNT precursor and put it into a quartz boat. Then put the quartz boat into a tubular furnace with a quartz tube. First, pass nitrogen for 30-60 minutes to expel the air in the quartz tube. Then switch the nitrogen to ammonia. Raise the temperature from room temperature to 400-600°C at a heating rate of 5-10°C / min. Keep the temperature for 2 hours after reaching the target temperature. Finally, cool it naturally and expel the ammonia in the quartz tube with nitrogen to obtain the final catalyst sample.

[0066] The catalyst prepared in this example exhibits excellent ORR performance in an acidic medium, with an ORR onset potential of 0.86 V vs. RHE and an ORR half-wave potential of 0.722 V vs. RHE.

[0067] Example 3

[0068] A method for preparing a carbon-supported niobium-based bimetallic nitrogen oxide catalyst (NbCrON / CB) comprises the following steps:

[0069] S31, pretreatment of carbon carrier;

[0070] Weigh 50-200 mg of carbon black (CB), add it into a 100-500 mL beaker, inject 3 / 5 volume of HNO3 (concentration of 1-4 mol / L) into the beaker, heat and reflux at 70-80 ° C for 8-12 h, finally filter the carbon support and wash it with deionized water until neutral, and then vacuum dry it in an oven at 60-80 ° C for 6-12 h to obtain a pretreated carbon support (CB).

[0071] S32, preparation of NbCrON / CB precursor;

[0072] 4-10 mmol potassium niobate and 1-10 mmol chromium chloride are weighed separately and dissolved in 30-80 ml of aqueous solution, and then 0.2-1 g of pretreated CB is added thereto, and after stirring for 1-2 hours, the mixture is filtered and dried to obtain a NbCrON / CB precursor.

[0073] Preparation of S33, NbCrON / CB catalyst;

[0074] Weigh 0.1-0.5 g of NbCrON / CB precursor and put it into a quartz boat. Then put the quartz boat into a tubular furnace with a quartz tube. First, introduce nitrogen for 30-60 minutes to expel the air in the quartz tube. Then switch the nitrogen to ammonia. Raise the temperature from room temperature to 600-800°C at a heating rate of 5-10°C / min. Keep the temperature for 2 hours after reaching the target temperature. Finally, cool it naturally and expel the ammonia in the quartz tube with nitrogen to obtain the final catalyst sample.

[0075] The catalyst prepared in this example exhibits excellent ORR performance in an acidic medium, with an ORR onset potential of 0.846 V vs. RHE and an ORR half-wave potential of 0.713 V vs. RHE.

[0076] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solutions disclosed in this disclosure can be achieved, and this document does not limit this.

[0077] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0078] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A method for preparing a catalyst based on carbon-supported niobium-based bimetallic oxynitride, characterized in that: The method comprises: Dissolving a niobium salt and another transition metal salt in water or an alcohol solution to prepare a precursor solution; the niobium salt is an oxygen-containing niobium salt, including one or more of potassium niobate, lithium niobate, sodium niobate, magnesium niobate, niobium oxalate, ammonium niobate oxalate, potassium niobate oxalate, lithium niobate oxalate, sodium niobate oxalate, rubidium niobate oxalate, and ethoxy niobium; The carbon carrier is uniformly dispersed in the precursor solution, and a precursor is obtained after filtering and drying; The precursor is calcined with a nitrogen source to obtain a carbon-supported niobium-based bimetallic oxynitride catalyst.

2. The method according to claim 1, characterized in that The concentration of the niobium salt in the precursor solution is 0.01-4 mol / L, and the concentration of the transition metal salt is 0.01-4 mol / L.

3. The method according to claim 1, characterized in that The transition metal salt includes one or more of chromium nitrate, chromium chloride, chromium sulfate, chromium acetate, manganese nitrate, manganese chloride, manganese sulfate, manganese acetate, ferric nitrate, ferric chloride, ferric sulfate, ferric acetate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, copper nitrate, copper chloride, copper sulfate, and copper acetate.

4. The method according to claim 3, characterized in that The niobium-based bimetallic oxynitrides include niobium-chromium oxynitride, niobium-manganese oxynitride, niobium-iron oxynitride, niobium-cobalt oxynitride, niobium-nickel oxynitride and niobium-copper oxynitride.

5. The method according to claim 1, characterized in that The carbon carrier includes one of XC-72R carbon black, Ketjenblack carbon black, carbon nanotubes, carbon nanofibers, graphene, MOF-derived carbon, and COF-derived carbon.

6. The method according to claim 1, characterized in that The precursor is calcined in an atmosphere of ammonia or nitrogen, at a temperature of 150 to 1000° C., for a time of 1 to 5 hours, at a heating rate of 1 to 20° C. / min.

7. The method according to claim 1, characterized in that The particle size of the carbon-supported niobium-based bimetallic oxynitride nanoparticles is 3-50 nm.

8. A catalyst based on carbon-supported niobium-based bimetallic oxynitride prepared according to the method of any one of claims 1 to 7.

9. Use of a carbon-supported niobium-based bimetallic oxynitride catalyst prepared according to the method of any one of claims 1 to 7 in a fuel cell.

Citation Information

Patent Citations

  • Electrode catalyst for fuel cell and its manufacture, and electrode and fuel cell using the catalyst

    JP1997167620A

  • Electrode catalyst for fuel cells, method for producing the same, and electrode for fuel cells

    JP2009208070A